Towards a New Flashmob Unionism: The Case of the Fight for 15 Movement. (2nd December 2019) - Pasquier, Vincent; Daudigeos, Thibault; Barros, Marcos
Abstract: Unionism renewal has been described as a hybridization process between 'old' and 'new' logics. Understanding how these two potentially conflicting logics might be combined, however, has so far received little attention. Through the study of the Fight for 15 (FF15) movement, we investigate how the old 'collectivist' logic of action‐oriented unions and the new 'connectivist' logic are being hybridized. To do so, we develop a mixed‐methods approach that combines interviews with Twitter data. We evidence three mechanisms through which the collectivist and connectivist logics are being hybridized, namely, imbrication, camouflage and cumulation. We suggest to name 'flashmob unionism' the hybrid logic of FF15, characterized by apparently spontaneous mobilizations, a loosely co‐ordinated organization, a personalized communication and online virality.